The ovoid lesion: a new MR observation in patients with multiple sclerosis. - Horowitz, A L; Kaplan, R D; Grewe, G; White, R T; Salberg, L M (American Journal of Neuroradiology, 1989)
We investigated the frequency of oval-shaped, high-signal-intensity lesions oriented perpendicular to the anteroposterior axis of the brain on abnormal, axial T2-weighted MR brain scans in 59 patients with clinically documented multiple sclerosis. This finding, not heretofore described in patients with multiple sclerosis, was observed in 86% of patients, and correlates with the neuropathologic description of demyelination in multiple sclerosis.